2018
DOI: 10.3389/fpsyg.2018.02136
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Anthropomorphism in Interaction: Intersubjectivity, Imagination, and Theory of Mind

Abstract: Human beings frequently attribute anthropomorphic features, motivations and behaviors to animals, artifacts, and natural phenomena. Historically, many interpretations of this attitude have been provided within different disciplines. What most interpretations have in common is distinguishing children’s manifestations of this attitude, which are considered “natural,” from adults’ occurrences, which must be explained by resorting to particular circumstances. In this article, I argue that anthropomorphism is not g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 75 publications
2
89
0
5
Order By: Relevance
“…A broad sample of effects has already been observed: a growing tendency to anthropomorphize is associated with a higher perceived credibility of a computer [17], and it predicts user satisfaction in the context of voice assistants [24]. The tendency to anthropomorphize inanimate objects can be especially observed in children [1,27]. Taking a look at their early development, it can be observed that children begin to show tendencies to personify their toys at a young age, which intensifies through emotional attachments [14].…”
Section: Anthropomorphizationmentioning
confidence: 99%
See 4 more Smart Citations
“…A broad sample of effects has already been observed: a growing tendency to anthropomorphize is associated with a higher perceived credibility of a computer [17], and it predicts user satisfaction in the context of voice assistants [24]. The tendency to anthropomorphize inanimate objects can be especially observed in children [1,27]. Taking a look at their early development, it can be observed that children begin to show tendencies to personify their toys at a young age, which intensifies through emotional attachments [14].…”
Section: Anthropomorphizationmentioning
confidence: 99%
“…Between the ages of three and five, a child gains the ability to perceive the emotional and mental states in others, which is commonly known as the theory of mind [28]. As the child gets older, the tendency to anthropomorphize diminishes [1,17]. Airenti [1] argues that on growing older, children develop the ability of more complex reflection processes.…”
Section: Anthropomorphizationmentioning
confidence: 99%
See 3 more Smart Citations